A Novel Electronegative Guest‐Filled Skutterudite‐Based Thermoelectric Generator with an Efficiency of 6.0%. Issue 9 (6th July 2022) - Wang, Boyu; Yi, Wen; Wang, Chengzhi; Jin, Haibo; Li, Jingbo
Abstract : Electronegative guest‐filled skutterudites (EN‐SKDs) are considered one of the most promising thermoelectric materials for next‐generation thermoelectric generators (TEGs). However, the practical application of EN‐SKDs in TEGs is still a huge challenge because of their unsatisfactory zT value (less than 1.0). Herein, Ge, Te‐codoped electronegative sulfur‐filled skutterudites of S x Co4 Sb11 Ge0.2 Te0.8 ( x  = 0, 0.05, 0.1, 0.2, 0.25) are synthesized. The optimal zT value of as high as 1.45 at 823 K with a low room‐temperature lattice thermal conductivity of 1.98 W m −1  K −1 is achieved by S0.25 Co4 Sb11 Ge0.2 Te0.8 . Such performance is competitive with those of traditional TE materials and among one of the best EN‐SKDs. The excellence is attributed to the synergistic effect of the disorder caused by Ge, Te co‐doping at Sb‐site and the "rattling" effect of electronegative element S. Furthermore, a novel EN‐SKD‐based TEG is prepared for the first time through an integrated welding process and exhibits a high efficiency of 6.0% at the temperature difference of 475 K. This work provides valuable guidance for designing advanced thermoelectric materials and paves a way toward high‐performance EN‐SKD‐based TEGs. Abstract : A series of electronegative S‐filled skutterudites S x Co4 Sb11 Ge0.2 Te0.8 ( x  = 0–0.25) are investigated, among which the optimal S0.25 Co4 Sb11 Ge0.2 Te0.8 exhibits excellent thermoelectric performance with a record high zT of 1.45 at 823 K. An electronegative element S‐filled skutterudites‐based thermoelectric generator is accordingly fabricated for the first time, which shows a promising conversion efficiency of 6.0% at the temperature difference of 475 K.